The Effect of Financial Leverage, Profitability and Dividend Policy on Firm Value - Qowiyyul Adib, Hanaf; Widiyanti, Marlina; Muhammad Husni Thamrin, Kemas; Andriana, Isni (Green Publisher Indonesia, 2024)
This research provides valuable insights into the factors influencing company value within the manufacturing sector, specifically the cement subsector in Indonesia. Financial leverage, profitability, and dividend policy are key variables examined, as they significantly impact a company's financial health and market perception. Financial leverage reflects a company’s reliance on debt financing relative to equity, and the study shows that higher leverage can positively affect company value if managed effectively, thereby increasing returns for shareholders. Profitability, often measured through indicators such as Return on Assets (ROA) or Return on Equity (ROE), also plays a significant role in enhancing company value, as it reflects efficient resource management and attracts investor interest. Additionally, a consistent dividend policy reinforces the company’s reputation and draws investors, contributing positively to company value in the stock market. The findings emphasize that cement subsector companies with balanced leverage, solid profitability, and a consistent dividend policy tend to perform better in terms of company value, providing essential insights for stakeholders in optimizing strategies to maximize company value.